2017
DOI: 10.1155/2017/4068963
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Anterior, Posterior, and Total Corneal Astigmatism after Descemet Membrane Endothelial Keratoplasty

Abstract: Purpose. To evaluate changes in anterior, posterior, and total corneal astigmatism in patients after Descemet membrane endothelial keratoplasty (DMEK). Methods. We retrospectively included 29 eyes of 23 patients (age 67.6 ± 9.8 years, 13 female, 10 male) after DMEK surgery. The magnitude and axis orientation of anterior, posterior, and total corneal astigmatism before and after DMEK were determined using a rotating Scheimpflug system (Pentacam HR, Oculus). Results. The magnitude of anterior, posterior, and tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
1
3
0
3
Order By: Relevance
“…Our findings are in accordance with a study performed by Yokogawa et al, which also showed a significant decrease in the magnitude of the posterior corneal astigmatism after DMEK surgery [19]. Along with a reduction of the magnitude of posterior corneal astigmatism, we also detected a shift in axis orientation to a higher proportion of eyes with ATR astigmatism, which is similar to results reported by Alnawaiseh et al [20]. In a study with nondiseased, previously unoperated eyes, total corneal astigmatism could not be predicted adequately by anterior measurements only, especially in eyes that do not have with-the-rule astigmatism, pointing out the relevance of posterior corneal profile [21].…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are in accordance with a study performed by Yokogawa et al, which also showed a significant decrease in the magnitude of the posterior corneal astigmatism after DMEK surgery [19]. Along with a reduction of the magnitude of posterior corneal astigmatism, we also detected a shift in axis orientation to a higher proportion of eyes with ATR astigmatism, which is similar to results reported by Alnawaiseh et al [20]. In a study with nondiseased, previously unoperated eyes, total corneal astigmatism could not be predicted adequately by anterior measurements only, especially in eyes that do not have with-the-rule astigmatism, pointing out the relevance of posterior corneal profile [21].…”
Section: Discussionsupporting
confidence: 93%
“… 17 There is also a concern about modification of the orientation of the posterior corneal astigmatism after DMEK; however, the change of its magnitude and orientation may or may not be significant. 18 …”
Section: Discussionmentioning
confidence: 99%
“…Since the introduction of the DMEK technique, changes in endothelial cell count (ECC), best corrected visual acuity (BCVA), and central corneal thickness (CCT) after surgery have been widely studied [7,[10][11][12][13]. ere are only a few reports analyzing postoperative corneal aberrations [14][15][16], keratometry [17][18][19], and astigmatism changes [20][21][22]. Regrettably, there are few studies that assess the dynamics of changes in corneal parameters over time in a detailed way.…”
Section: Introductionmentioning
confidence: 99%